Prospects and principles for the creation of the "Dictionary of Agricultural Names of Central Slobozhanshchyna (Kharkiv Region)" - Сердега, Руслан Леонідович (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
The growing interest in the study of the Ukrainian regional speech and the activation of attempts at its lexicographic representation are directly related to the two primary tasks of modern Ukrainian dialectological science. Such priority tasks of Ukrainian dialectology are the preparation of the Lexical Atlas of the Ukrainian language and drawing up the summary dialect dictionary today. The fulfillment of these tasks is possible only if the lexicographic representation of all local dialects of the Ukrainian language is more or less adequate. The "Dictionary of Agricultural Names of the Central Slobozhanshchina (Kharkiv Region)", developed by us, can contribute to a broader representation of the Central Slobozhanshchyna dialect. The purpose of our article is to cover the basic principles of compiling the dictionary entries of the "Dictionary of Agricultural Names of Central Slobozhanshchyna (Kharkiv Region)". Stacking dictionaries of various types has always been one of the most important practical tasks of linguistic science. Of course, dialectal vocabulary also plays a role in relation to such a practical orientation of linguistics. Regional (dialectal) dictionaries can fix and keep the elements of the living broadcasting are already lost by a literary language. They enrich the national spiritual potential, the general cultural fund of the people, reflect the origins of the national consciousness of the Ukrainian peasant. Such dictionaries directly reflect important fragments of the linguistic picture of the Ukrainian world. In the article we will also demonstrate the lexical and phraseological material of the dictionary developed by us. At the moment we have prepared a draft version of the "Dictionary of Agricultural Names of Central Slobozhanshchyna (Kharkiv Region)". It still contains dictionary entries for the letters A-G so far. We see the prospects of further scientific research in creation of the full "Dictionary of agricultural names of the Central Slobozhanshchina (Kharkiv region)".